101k views
1 vote
Math Question: Had issues factoring, can anyone help?

Math Question: Had issues factoring, can anyone help?-example-1

1 Answer

7 votes

Answer:

x(x - 4)(x + 1)

Explanation:

x³ - 3x² - 4x ← factor out x from each term

= x(x² - 3x - 4) ← factor the quadratic

consider the factors of the constant term (- 4) which sum to give the coefficient of the x- term (- 3)

the required factors are - 4 and + 1 , since

- 4 × + 1 = - 4 and - 4 + 1 = - 3 , then

x²- 3x - 4 = (x - 4)(x + 1)

and

x³ - 3x² - 4x = x(x - 4)(x + 1)

User IrAM
by
5.0k points